Rethinking Stravinsky historically and theoretically - Glivinsky, Valery (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
A new perspective is proposed on the evolution of musical culture in the 20th century. Within this process, the central position occupied by the work of the St. Petersburg Classic School – Stravinsky, Prokofiev, and Shostakovich – is highlighted. For a more profound understanding of Stravinsky’s music, the categorical pair of the morpheme and morph is introduced for use in musical analysis. The morphic realization of the morphemes of the environment, motion, space, and dissonance, and the Janus morpheme, is traced in the text of the romance Spring (Cloister Song) and in the Introduction to the ballet The Rite of Spring. An essential conclusion is drawn regarding the polymorphic nature of the musical fabric in the Russian master’s works.